Beneficial Effects of Tocotrienol and Tocopherol on Bone Histomorphometric Parameters in Sprague–Dawley Male Rats After Nicotine Cessation - Hapidin, Hermizi; Othman, Faizah; Soelaiman, Ima-Nirwana; Shuid, Ahmad Nazrun; Mohamed, Norazlina (2009)
This study was conducted to determine the effectiveness of three forms of vitamin E supplements following nicotine treatment on bone histomorphometric parameters in an adult male rat model. Rats were divided into seven groups: baseline (B, killed without treatment), control (C, normal saline for 4 months), nicotine (N, nicotine for 2 months), nicotine cessation (NC), tocotrienolenhanced fraction (TEF), gamma-tocotrienol (GTT), and alpha-tocopherol (ATF). Treatments for the NC, TEF, GTT, and ATF groups were performed in two phases. For the first 2 months they were given nicotine (7 mg/kg), and for the following 2 months nicotine administration was stopped and treatments with respective vitamin E preparations (60 mg/kg) were commenced except for the NC group, which was allowed to recover without treatment. Rats in the N and NC groups had lower trabecular bone volume, mineral appositional rate (MAR), and bone formation rate (BFR/BS) and higher single labeled surface and osteoclast surface compared to the C group. Vitamin E treatment reversed these nicotine effects. Both the TEF and GTT groups, but not the ATF group, had a significantly higher trabecular thickness but lower eroded surface (ES/BS) than the C group. The tocotrienol-treated groups had lower ES/BS than the ATF group. The GTT group showed a significantly higher MAR and BFR/BS than the TEF and ATF groups. In conclusion, nicotine induced significant bone loss, while vitamin E supplements not only reversed the effects but also stimulated bone formation significantly above baseline values. Tocotrienol was shown to be slightly superior compared to tocopherol. Thus, vitamin E, especially GTT, may have therapeutic potential to repair bone damage caused by chronic smoking.